Salut!
[tex](2 + 2 \times 3) \times (2 \times 2^{2} \times {2}^{3} \div 2^{6} + (3^{10} \div {3}^{6} - ( {3}^{2} ) ^{2} ) + {16}^{0} < = > [/tex]
[tex](2 + 6) \times (2 \times {2}^{2} \times {2}^{3} \div {2}^{6} + ( {3}^{10} \div {3}^{6} - {3}^{4} ) ) + {16}^{0} < = > [/tex]
[tex]8 \times ( {2}^{1} \times {2}^{2} \times {2}^{3} \div {2}^{6} + ( {3}^{4} - {3}^{4}) ) + {16}^{0} < = > [/tex]
[tex]8 \times ( {2}^{1} \times {2}^{2} \times {2}^{3} \div {2}^{6} + 81) + {16}^{0} < = > [/tex]
[tex]8 \times ( {2}^{3} \times {2}^{3} \div {2}^{6} + 81) + 16^{0} < = > [/tex]
[tex]8 \times (2^{6} \div {2}^{6} + 81) + 16^{0} < = > [/tex]
[tex]8 \times (1 + 81) + 16^{0} < = > [/tex]
[tex]8 \times 82 + 1 < = > [/tex]
[tex]656 + 1 < = > [/tex]
[tex]657[/tex]